Menemukan Konsep Ideal Hubungan Pusat dan Daerah dalam Bingkai Negara Kesatuan Republik Indonesia - Afandi, Ahmad; Basuki, Udiyo (Universitas Proklamasi 45, 2023)
Indonesia is a unitary state or negara kesatuan. One of the characteristics of a unitary state is the concentration of all forms of policy on the central government. In other words, the central government has very broad authority in regulating policies in the regions. On the other hand, policies that tend to be more centralized can cause injustice to diversity in the regions, especially for Indonesia, which is geographically an archipelagic country that has very diverse customs and cultures, so the needs in each region are very complex.Therefore, this paper offers a system of residual asymmetric decentralization that can be applied in Indonesia by rigidly dividing the authority of the central and regional governments. Such a division of authority is an urgent matter so that there is no longer any authority overlap between the central and regional governments. Besides that, the distribution of authority in this way can also further emphasize the characteristics of decentralization within the framework of the Unitary State of the Republic of Indonesia.